3D-QSAR, molecular docking and molecular dynamics simulations analyses of a series of heteroaryldihydropyrimidine derivatives as hepatitis B virus capsid assembly inhibitors. (17th November 2021) - Chen, Lu; Liu, Wen-Guang; Xiong, Fei; Ma, Chao; Sun, Chen; Zhu, Yi-Ren; Zhang, Xing-Guang; Wang, Zhong-Hua
Abstract : In silico design of heteroaryldihydropyrimidine-based selective HBV capsid assembly inhibitors. Abstract : The HBV capsid protein (CP) plays a vital role in the multiple life cycles of HBV and represents a novel anti-HBV target. Recently, a novel series of heteroaryldihydropyrimidine (HAP) derivatives were reported as potent inhibitors of HBV capsid assembly, and they also exhibit antiviral activities. In this study, the structure and activity relationship of 36 heteroaryldihydropyrimidine-based compounds was explored by conducting structure–activity relationship (3D-QSAR) studies using CoMFA and CoMSIA models. The results showed that CoMFA ( q 2 = 0.610, r 2 = 0.998, and r pred 2 = 0.837) and CoMSIA ( q 2 = 0.586, r 2 = 0.998, and r pred 2 = 0.698) have excellent estimation stability and prediction capability. The contour maps of the steric field, electrostaticfield, and hydrogen bond acceptor field revealed the modified regions of these compounds. Subsequently, molecular docking was carried out to investigate the docking mode of the template molecule and receptors, thereby further verifying the results of the 3D-QSAR model. Molecular dynamics (MD) simulations were performed to validate the accuracy of the docking results. Based on these results, we designed 4 new heteroaryldihydropyrimidine-based compounds and predicted their activity. These results may provide important reference for the design and development of potent and new HBV capsid assembly inhibitors.